Global variation in grip strength: a systematic review and meta-analysis of normative data - Dodds, Richard M; Syddall, Holly E; Cooper, Rachel; Kuh, Diana; Cooper, Cyrus; Sayer, Avan Aihie (Age and ageing, 2016)
weak grip strength is a key component of sarcopenia and is associated with subsequent disability and mortality. We have recently established life course normative data for grip strength in Great Britain, but it is unclear whether the cut points we derived for weak grip strength are suitable for use in other settings. Our objective was to investigate differences in grip strength by world region using our data as a reference standard. we searched MEDLINE and EMBASE for reporting age- and gender-stratified normative data for grip strength. We extracted each item of normative data and converted it on to a Z-score scale relative to our British centiles. We performed meta-regression to pool the Z-scores and compare them by world region. our search returned 806 abstracts. Sixty papers met inclusion criteria and reported on 63 different samples. Seven UN regions were represented, although most samples (n = 44) were based in developed regions. We extracted 726 normative data items relating to 96,537 grip strength observations. Normative data from developed regions were broadly similar to our British centiles, with a pooled Z-score 0.12 SDs (95% CI: 0.07, 0.17) above the corresponding British centiles. By comparison, normative data from developing regions were clearly lower, with a pooled Z-score of -0.85 SDs (95% CI: -0.94, -0.76). our findings support the use of our British grip strength centiles and their associated cut points in consensus definitions for sarcopenia and frailty across developed regions, but highlight the need for different cut points in developing regions.